Diversity, spatial distribution and evolution of inactive and weakly active hydrothermal deposits in the TAG hydrothermal field - Pelleter, Ewan-Loiz; Principaud, Mélanie; Alix, Anne-Sophie; Boissier, Audrey; Cheron, Sandrine; Besson, Florian; Altorffer, Vincent; Guérin, Charline; Gaillot, Arnaud; Pierre, Delphine; Rospabé, Mathieu; Giunta, Thomas; et al. (Frontiers in Earth Science, 2024)
Although, there is an increasing focus on inactive or extinct seafloor massive sulfide (SMS) deposits driven by the possibility of marine mining, only few studies have been devoted to them so far. The Trans-Atlantic Geotraverse (TAG) hydrothermal field is the first hydrothermal vent discovered on the Mid-Atlantic Ridge and probably one of the best-studied hydrothermal systems. Relict SMS deposits within the TAG field are known since the mid-1980s but these so-called inactive sites have only been recently further investigated with limited dive observations, sampling and in-situ temperature measurements. High-resolution acoustic surveys and extensive human occupied vehicle (HOV) dive operations performed during four different expeditions led to the discovery of thirteen new hydrothermal mounds including six large (i.e > 5000 m 2 ) deposits making the TAG hydrothermal field one of the largest accumulation of hydrothermal materials (21.1 Mt) known on the seafloor. However, copper and zinc grades of the largest SMS deposits remain low (i.e. < 1.4 wt.%) even compared to onland volcanogenic massive sulfide deposits. Additionally, eight areas of diffuse hydrothermal fluid flow were identified challenging the presumed inactivity of these SMS deposits and, for the first time, emphasizing the importance of low temperature (LT) hydrothermal activity in whole the TAG field.Inactive and weakly active SMS deposits exhibit a large diversity of surface mineralization (e.g. sulfides, Fe-Mn mineralization, jasper) illustrating complexity of hydrothermal activities but also different ageing history. Several mounds no longer have visible sulfide chimneys and are covered by a widespread layer of manganese and iron oxyhydroxides attesting the longevity of diffuse fluid flow at specific locations even long after last high-temperature (HT) hydrothermal activity has ceased. This contrasts with SMS deposits that are devoid of extensive LT precipitates but characterized by standing or topped sulfide chimney indicating a relatively abrupt cessation of HT hydrothermal activity.Together these results allow us to propose evolution models to explain the diversity of active, weakly active and inactive SMS deposits in the TAG hydrothermal field.